Navigating the Disruption of Digital and Conventional Media in Changing Media Consumption Landscape in Digital Era - Mohammad Alzub, Ahmad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
The landscape of media consumption has undergone a significant transformation as a direct result of the proliferation of digital media in our century. This research study investigates the impact that digital media has had on traditional media formats, such as print, broadcast, and advertising. Specifically, the author investigates how the proliferation of digital platforms has had an effect on traditional media formats. This article examines the numerous ways in which digital media has disrupted traditional media by doing a thorough assessment of the available literature and conducting an analysis of the various ways in which digital media has changed consumer behaviour, business models, content generation, and distribution. Additionally, this article explores the difficulties and possibilities that traditional media confront in this age of digital technology and offers suggestions for how scholars and practitioners in the field of media might adapt to and succeed in this shifting environment.